2010
DOI: 10.4315/0362-028x-73.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol and Cinnamaldehyde Inactivate Antibiotic-Resistant Salmonella enterica in Buffer and on Celery and Oysters

Abstract: The emergence of antibiotic-resistant Salmonella is of concern to food processors. The objective of this research was to identify antimicrobial activities of cinnamaldehyde and carvacrol against antibiotic-resistant Salmonella enterica in phosphate-buffered saline (PBS) and on celery and oysters. Twenty-three isolates were screened for resistance to seven antibiotics. Two resistant and two susceptible strains were chosen for the study. S. enterica cultures (10(5) CFU/ml) were added to different concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 47 publications
4
60
0
1
Order By: Relevance
“…The antimicrobial effect of EOs has been reported to be concentration dependent (Sivropoulou et al 1996). Ravishankar et al (2010) reported that at a 0.2% concentration, antimicrobials, carvacrol and cinnamaldehyde completely inactivated the antibiotic-resistant and -susceptible isolates of S. enterica. Zhou et al combination against S. Typhimurium, and reported the lowest concentrations of cinnamaldehyde, thymol and carvacrol inhibiting the growth of S. Typhimurium significantly were 200, 400 and 400 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial effect of EOs has been reported to be concentration dependent (Sivropoulou et al 1996). Ravishankar et al (2010) reported that at a 0.2% concentration, antimicrobials, carvacrol and cinnamaldehyde completely inactivated the antibiotic-resistant and -susceptible isolates of S. enterica. Zhou et al combination against S. Typhimurium, and reported the lowest concentrations of cinnamaldehyde, thymol and carvacrol inhibiting the growth of S. Typhimurium significantly were 200, 400 and 400 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The main constituent of the T. capitata hydrosol is carvacrol, with a concentration of 943.6 mg/liter (0.0943%). Several studies have demonstrated that carvacrol has both bacteriostatic and bactericidal activity against foodborne microorganisms, including Salmonella enterica (27,(73)(74)(75). The effectiveness of carvacrol as a natural antimicrobial compound is well established, and its mechanism of action is believed to be associated with structural and functional damage to cellular membranes (25,28,(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…This strain is resistant to amoxicillin-clavulanic acid, ampicillin, cefoxitin, chloramphenicol, streptomycin, and tetracycline (Ravishankar et al 2010). Stock culture of the organism was maintained in cryovials (Microbank TM Austin, TX, USA.)…”
Section: Materials and Methods Bacterial Culture And Mediamentioning
confidence: 99%
“…Moore-Neibel et al (2013) found that oregano oil was effective against S. Newport on organic leafy greens and Ravishankar et al (2010) found that cinnamaldehyde, the antimicrobial component in cinnamon leaf oil, and carvacrol, inactivated Salmonella serovars in vitro and S. Newport on celery and oysters.…”
mentioning
confidence: 99%